TREATMENT OF INCOME TAXES IN CORPORATION INCOME STATEMENTS. - Greer, Howard C. (The Accounting Review, 1945)
Abstract The article presents information on treatment of income taxes in corporation income statements. The provision for income and excess profits taxes has become a very important item in the income statement of most corporations. In determining the amount, description and placement of this item in the statement, the following questions may require consideration: (1) should federal and state income and excess profits taxes be treated as (a) a cost of doing business, or (b) a distribution of profits? (2) if the earnings of an enterprise for a fiscal period are partly from ordinary operations and partly from special nonrecurring transactions, should the amount of tax applicable to each class of earnings be separately deducted from such earnings or should all earnings of the enterprise first be combined into one figure and the total income and excess profits tax deducted in a single sum? (3) If an allocation of the tax total between classes of income is permissible, may the same principle be applied if one class of transactions has resulted in a profit and the other in a loss? That is, may the statement be arranged to show the saving in taxes as a deduction from the loss, while the full tax without benefit of the saving is deducted from the profit?